Grid Technology: Enabling Scalable Virtual Organizations - Imran Khan; Nasir Tauheed (JISR Management and Social Sciences & Economics, 2004)
“Grid” computing has emerged as an important new field, distinguished from conventional distributed computing by its focus on large-scale resource sharing, innovativeapplications, and, in some cases, high-performance orientation. In this report, we define this new field. First, we review the “Grid problem,” which we define as flexible,secure, coordinated resource sharing among dynamiccollections of individuals, institutions, and resources—what we refer to as virtual organizations. We describerequirements that we believe any such mechanisms must satisfy and we discuss the importance of defining a compact set of intergrid protocols to enable interoperability among different Grid systems. Finally, we discuss how Gridtechnologies relate to other contemporary technologies,including enterprise integration, application serviceprovider, storage service provider, and peer-to-peer computing. We maintain that Grid concepts and technologies complement and have much to contribute to these otherapproaches.